Incomplete-Information Models of Guilt Aversion in the Trust Game - Attanasi, Giuseppe; Battigalli, Pierpaolo; Manzoni, Elena (Management Science, 2016)
In the theory of psychological games it is assumed that players’ preferences on material consequences depend on endogenous beliefs. Most of the applications of this theoretical framework assume that the psychological utility functions representing such preferences are common knowledge. However, this is often unrealistic. In particular, it cannot be true in experimental games where players are subjects drawn at random from a population. Therefore, an incomplete-information methodology is needed. We take a first step in this direction, focusing on guilt aversion in the Trust Game. In our models, agents have heterogeneous belief hierarchies. We characterize equilibria where trust occurs with positive probability. Our analysis illustrates the incomplete-information approach to psychological games and can help to organize experimental results in the Trust Game. This paper was accepted by Uri Gneezy, behavioral economics.